Mantle cell lymphoma cells express high levels of CXCR4, CXCR5, and VLA-4 (CD49d): importance for interactions with the stromal microenvironment and specific targeting - Kurtova, Antonina V. (Blood, 2009)
Mantle cell lymphoma (MCL) is characterized by an early, widespread dissemination and residual disease after conventional treatment, but the mechanisms responsible for lymphoma cell motility and drug resistance are largely unknown. There is growing evidence suggesting that chemokine receptors and adhesion molecules are critical for malignant B-cell trafficking and homing to supportive tissue microenvironments, where they receive survival and drug resistance signals. Therefore, we examined chemokine receptor and adhesion molecule expression and function in MCL cells and their importance for migration and adhesion to marrow stromal cells (MSCs). We found that MCL cells display high levels of functional CXCR4 and CXCR5 chemokine receptors and VLA-4 adhesion molecules. We also report that MCL cells adhere and spontaneously migrate beneath MSCs in a CXCR4- and VLA-4–dependent fashion (pseudoemperipolesis). Moreover, we demonstrate that MSCs confer drug resistance to MCL cells, particularly to MCL cells that migrate beneath MSC. To target MCL-MSC interactions, we tested Plerixafor, a CXCR4 antagonist, and natalizumab, a VLA-4 antibody. Both agents blocked functional responses to the respective ligands and inhibited adhesive interactions between MCL cells and MSCs. These findings provide a rationale to further investigate the therapeutic potential of these drugs in MCL.